2022
DOI: 10.3390/antiox11071405
|View full text |Cite
|
Sign up to set email alerts
|

Maqui (Aristotelia chilensis (Mol.) Stuntz): A Natural Antioxidant to Improve Quality of Meat Patties

Abstract: Aristotelia chilensis is an endemic shrub of the South Pacific with high concentrations of bioactive compounds in its leaves and, therefore, it is highly valued. The effect of Aristotelia chilensis leaf powders (maqui leaf powders; Ma) on the quality and shelf life of beef patties during 7 days of storage was investigated. Five beef patties treatments were prepared: (1) Control without antioxidants (CT); (2) Beef patties with synthetic antioxidants plus color (250 mg/kg) (PL); (3) Beef patties with 500 ppm of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 61 publications
(114 reference statements)
0
4
0
1
Order By: Relevance
“…In a study where researchers compared control patties without antioxidants, patties added with synthetic antioxidants, and patties added with Maqui leaf powders in concentrations of 500, 1000, and 2000 ppm, it was found that the pH of the control beef patties increased during storage, while the pH of beef patties with synthetic and natural antioxidants decreased; furthermore, decreased lipid oxidation was observed in patties added with Maqui (at all doses) in comparison with the synthetic antioxidant. With respect to organoleptic characteristics, redness (a*) was affected at doses of 1000 ppm and 2000 ppm of Maqui powder; despite this, the incorporation of this product did not affect the general acceptability of the patties, concluding that this natural additive can be used in the formulation of beef patties [ 56 , 57 ].…”
Section: Applications Of Maqui Fruit In the Food Industrymentioning
confidence: 99%
“…In a study where researchers compared control patties without antioxidants, patties added with synthetic antioxidants, and patties added with Maqui leaf powders in concentrations of 500, 1000, and 2000 ppm, it was found that the pH of the control beef patties increased during storage, while the pH of beef patties with synthetic and natural antioxidants decreased; furthermore, decreased lipid oxidation was observed in patties added with Maqui (at all doses) in comparison with the synthetic antioxidant. With respect to organoleptic characteristics, redness (a*) was affected at doses of 1000 ppm and 2000 ppm of Maqui powder; despite this, the incorporation of this product did not affect the general acceptability of the patties, concluding that this natural additive can be used in the formulation of beef patties [ 56 , 57 ].…”
Section: Applications Of Maqui Fruit In the Food Industrymentioning
confidence: 99%
“…Several compounds generated during the oxidative degradation of meat lipids have potential negative health effects 2 . Consequently, the industry and the scientific community have tried to minimize the accumulation of oxidation products during processing through different technologies and/or by the use of antioxidants, with particular interest in those of natural origin 3 …”
Section: Introductionmentioning
confidence: 99%
“…2 Consequently, the industry and the scientific community have tried to minimize the accumulation of oxidation products during processing through different technologies and/or by the use of antioxidants, with particular interest in those of natural origin. 3 Different types of herbs or their extracts, or even waste products obtained from vegetable sources have been used in meats and meat products trying to extend their shelf life, limiting or reducing the lipid and protein oxidation processes. [4][5][6][7] Among them, the use of aromatic herbs which have been traditionally used for improving the sensory properties of meat dishes are of great interest.…”
Section: Introductionmentioning
confidence: 99%
“…Principal plant pigments comprised chlorophyll (green), anthocyanins (blue-red), carotenoids (yellow-orange), and betalains (red-purple-yellow) (Novais et al, 2022;Zhang et al, 2022). In this course, numerous studies investigated the potential of plant extracts, such as maqui (Aristotelia chilensis) (Velázquez et al, 2022), red pitaya (Bellucci et al, 2021), Bixa Orellana (Bolognesi and Garcia, 2018), red prickly pear pulp (Kharrat et al, 2018;Palmeri et al, 2018), and jabuticaba (Myrciaria cauliflora) (Baldin et al, 2018;Tayebeh et al, 2021), for meat and meat products. It must be noted that color is the principal sensory quality influencing a food product's initial perception and market success (Manzoor et al, 2021).…”
Section: Introductionmentioning
confidence: 99%